Performance of the European Working Group on Sarcopenia in Older People algorithm in screening older adults for muscle mass assessment. - Lourenço, Roberto Alves; Pérez-Zepeda, Mario; Gutiérrez-Robledo, Luis; García-García, Francisco J.; Rodríguez Mañas, Leocadio (Age & Ageing, 2015)
Background: there is a lack of consensus on the diagnosis of sarcopenia. A screening and diagnostic algorithm was proposed by the European Working Group on Sarcopenia in Older People (EWGSOP).Objective: to assess the performance of the EWGSOP algorithm in determining the proportion of subjects suspected of having sarcopenia and selected to undergo subsequent muscle mass (MM) measurement.Design: a cross-sectional study.Setting: the cohorts, Frailty in Brazilian Older People Study—Rio de Janeiro (FIBRA-RJ), Brazil; Coyoacan Cohort (CC), Mexico City, Mexico; and Toledo Study for Healthy Aging (TSHA), Toledo, Spain.Subjects: three thousand two hundred and sixty community-dwelling individuals, 65 years and older.Methods: initially, the EWGSOP algorithm was applied using its originally proposed cut-off values for gait speed and handgrip strength; in the second step, values tailored for the specific cohorts were used.Results: using the originally suggested EWGSOP cut-off points, 83.4% of the total cohort (94.4% in TSHA, 75.5% in FIBRA-RJ, 67.8% in CC) would have been considered as suspected of sarcopenia. Adapted cut-off values lowered the proportion of abnormal results to 34.2% (quintile-based approach) and 23.71% (z-score approach).Conclusions: the algorithm proposed by the EWGSOP is of limited clinical utility in screening older adults for sarcopenia due to the high proportion of subjects selected to further undergo MM assessment. Tailoring cut-off values to specific characteristics of the population being studied reduces the number of people selected for MM assessment, probably improving the performance of the algorithm. Further research including the objective measure of MM is needed to determine the accuracy of these specific cut-off points.